2016
DOI: 10.1016/j.rpor.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous medulloblastoma and glioblastoma: Implications for clinical and technical aspects of re-irradiation

Abstract: Glioblastoma Re-irradiation Brainstem tolerance Toxicity a b s t r a c tA seven-year-old male underwent surgical resection and chemoradiation for average risk medulloblastoma; twelve years later, the presence of a necrotic and infiltrative mass in the same area and invading the brainstem prompted a subtotal resection. Pathology was indicative of glioblastoma. He was then treated with concurrent temozolomide and using biologically effective dose calculations for gross residual tumor tissue in the brainstem as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Biopsies are rarely performed at relapse and the absence of data about the tumour characteristics may challenge the selection of effective second-line therapeutic strategies. In addition, studies comparing primary versus relapse tumours have shown that other mutations can arise in the recurrent tumour and that secondary tumours can be completely different from the primary tumour [11][12][13][14] . In this study, we have shown that WES of CSF ctDNA can characterise the disease at relapse, including the detection of CSF-private mutations that reveal the intratumour/interlesion heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biopsies are rarely performed at relapse and the absence of data about the tumour characteristics may challenge the selection of effective second-line therapeutic strategies. In addition, studies comparing primary versus relapse tumours have shown that other mutations can arise in the recurrent tumour and that secondary tumours can be completely different from the primary tumour [11][12][13][14] . In this study, we have shown that WES of CSF ctDNA can characterise the disease at relapse, including the detection of CSF-private mutations that reveal the intratumour/interlesion heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of primary and relapsed tumours has shown that specific molecular alterations can appear in the relapse setting 10 , 11 . In addition, secondary radiotherapy-induced tumours can emerge in some patients 12 14 . To assess metastatic dissemination, cerebrospinal fluid (CSF) cytology together with brain and spinal MRI are performed and patients are classified according to Chang M-staging system 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The biologically effective dose (BED) was calculated using the linear-quadratic (LQ) model with a α/β ratio of 3 Gy, following established methods outlined in previous studies [11,12]. BED values were subsequently converted to SFED and equivalent total doses in 2-Gy fractions (EQD2) using LQ model [13].…”
Section: Biologically Effective Dose (Bed) Single-fraction Equivalent...mentioning
confidence: 99%
“…The biologically effective dose (BED) was calculated using the linear-quadratic (LQ) model with a α/β ratio of 3 Gy [11,12]. The BED was converted to SFED and the equivalent total doses in 2-Gy fractions (EQD2) using LQ model [13].…”
Section: Biologically Effective Dose (Bed) Single-fraction Equivalent...mentioning
confidence: 99%